STRATEGI PEMANFAATAN OBJEK WISATA PANTAI CAROCOK GUNA MENINGKATKAN KETAHANAN EKONOMI PENDUDUK PESISIR - Ahsan, Ahmad Nur; Mardjitulastri; Hifni, Muchammad; Irfan, Muhammad (PPM Sdirjianbang Akademi Militer, 2023)
Tourism has an important role in regional economic development, especially in coastal areas. Carocok beach tourist attraction in Nagari Painan Selatan, District IV Jurai, Pesisir Selatan Regency, is one of the promising tourism potentials. However, there has been no study that comprehensively examines the strategy of utilizing Carocok beach tourism objects to increase the economic resilience of coastal residents in the region. Community Service through this research aims to analyze the strategy of utilizing Carocok beach tourism objects to increase the economic resilience of coastal residents and contribute to the development of Carocok beach tourism and provide input for local governments and related stakeholders to formulate sustainable tourism development strategies that have a positive impact on the local community.